2014
DOI: 10.1371/journal.pone.0111058
|View full text |Cite
|
Sign up to set email alerts
|

From Moderately Severe to Severe Hypertriglyceridemia Induced Acute Pancreatitis: Circulating MiRNAs Play Role as Potential Biomarkers

Abstract: The incidence of hypertriglyceridemia induced acute pancreatitis (HTAP) continues to rise in China. It has systemic complications and high mortality, making the early assessment of the severity of this disease even more important. Circulating microRNAs (miRNAs) could be novel, non-invasive biomarkers for disease progression judgment. This study aimed to identify the potential role of serum miRNAs as novel biomarkers of HTAP progression. HTAP patients were divided into two groups: moderately severe (HTMSAP) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 39 publications
2
23
0
Order By: Relevance
“…To date, a few studies have examined circulating miRNAs in patients with pancreatitis and have sought to identify miRNAs that are predictive for the diagnosis or prognosis of pancreatitis3536. However, there is no study about the potential biomarkers for the early diagnosis of CP.…”
Section: Discussionmentioning
confidence: 99%
“…To date, a few studies have examined circulating miRNAs in patients with pancreatitis and have sought to identify miRNAs that are predictive for the diagnosis or prognosis of pancreatitis3536. However, there is no study about the potential biomarkers for the early diagnosis of CP.…”
Section: Discussionmentioning
confidence: 99%
“…Kuśnierz-Cabala B et al demonstrated that the expression levels of miR-126-5p, miR-148a-3p, miR-216a-5p, miR-551b-5p and miR-375 were significantly elevated in moderate and severe acute pancreatitis (SAP) when compared to control subjects; however, in mild acute pancreatitis (MAP) patients, only miR-216a-5p, miR-551b-5p, and miR-375 were highly expressed [13]. Ma X et al reported that miR-21 was overexpressed in a murine model of AP [14], and An F et al discovered that miR-24-3p, miR-361-5p, miR-1246 and miR-222-3p were constantly up-regulated, and miR-181a-5p was constantly down-regulated, in hypertriglyceridemia-induced acute pancreatitis patients [15]. Moreover, it has been reported that miR-375, miR-217, miR-148a, miR-216a, miR-122, miR-214 and miR-138 were increased in mesenteric lymph nodes from rats with AP, and miR-217, miR-375, miR-122 and miR-148a were also increased in matched rat plasma samples [16].…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies [21][22][23][24][25] also show that the HTG induced by high-cholesterol diets, triglyceride infusion or the injection of an active detergent (Triton WR 1339) intensifies the course of pancreatitis. These findings support that both of endogenous and exogenous HTG increases susceptibility to acute pancreatitis.…”
Section: Pancreatic Histopathologic Examinationmentioning
confidence: 53%